Fast handover algorithm for hierarchical mobile IPv6 macro-mobility management - Vivaldi, Indra; Habaebi, Mohamed Hadi; Mohd Ali, Borhanuddin; V., Prakash (IEEE, 2003)
Mobile lh.6 (MIPv6) has some limitations due to long delays and signaling load during handover operation. Hierarchical Mobile IPv6 (HMIPv6) is the extension of MIPv6 that is designed to reduce the signaling load and to improve handover speed of MIPv6 by splitting the mobility management into macro and micro mobility management schemes. However HhfIPv6 only improves micro mobility problem where the signifcant delay still occurs in the macro mobility management because the handover algorithm is similar with the MIPv6 environment, This paper proposes a new fast handover algorithm that overcomes the limitations in Mobile MIPv6 and its extension HMIPv6. Our design objective is to re-establish the communication traffic flow quickly and to minimize the service disruption delay that occnrs during handover process in a macro mobility environment. This handover algorithm is based on the modification of the HMIPv6 protocol using the multicast technique concept. This algorithm will enable the mobile node to receive packet faster than HMIPv6 protocol during handover, seamlessly and transparently. Keywords: Mobile lPv6, HMPv6, Hondover. Mufticart Scheme